1x+6=-7x+2/3

Simple and best practice solution for 1x+6=-7x+2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x+6=-7x+2/3 equation:


x in (-oo:+oo)

1*x+6 = 2/3-7*x // - 2/3-7*x

1*x-(-7*x)-(2/3)+6 = 0

x+7*x-2/3+6 = 0

8*x+16/3 = 0 // - 16/3

8*x = -16/3 // : 8

x = -16/3/8

x = -2/3

x = -2/3

See similar equations:

| x^2+4x=28+x | | X+6=-7x+2/3 | | 0=5x+7+2x-16 | | 5(9g+9)= | | 2(x-6)-4x= | | 175/5-1=t | | 17.5+4.5=1.75-.75y | | 2x+(x-1)=23 | | 3/5x15=x | | 48(4-2x)=12 | | 3x+36-2x=44 | | 8/x+3-7/x-2 | | d^2-11d+18=0 | | 2(3x+1)(2x-9)=0 | | X+6=-7+2/3 | | y=4sin(3pix+4) | | 2x-9y=35 | | 7x^2-13x-12=0 | | 1/5/175-1 | | 2/3y=9/4 | | 86p+42(1-p)=36p+106(1-p) | | 2+n/3=-1 | | x+17=-2X-7 | | 1x+10y=129000 | | 2x-(14-x)=1 | | x^2-15x=-5 | | 2x-7/5+x+1/3=7 | | x^2+9=44-4x | | -x*0=0 | | 2.5/15 | | 4x^2+8x+82=0 | | x+1/3+5=x+6/9 |

Equations solver categories